1999
DOI: 10.1063/1.369426
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cu gettering to H+ and He+ implantation-induced cavities in separation-by-implantation-of-oxygen wafers

Abstract: Articles you may be interested inIncreased thickness of buried oxide layer of silicon on insulator in separation by implantation of oxygen with water plasma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…25,26 Earlier studies have shown that, after 1 h annealing in air at 1000°C, platelets containing oxygen are formed on the remnants of the hydrogen platelets. 13,20 Figure 8 shows the n-type Cz Si after annealing for 1 h at 1000°C.…”
Section: Segregation Of Impuritiesmentioning
confidence: 99%
“…25,26 Earlier studies have shown that, after 1 h annealing in air at 1000°C, platelets containing oxygen are formed on the remnants of the hydrogen platelets. 13,20 Figure 8 shows the n-type Cz Si after annealing for 1 h at 1000°C.…”
Section: Segregation Of Impuritiesmentioning
confidence: 99%
“…The ''surface'' or areal density of trapped sites on the cavity walls after 1000°C annealing is calculated to be 3.5 ϫ10 15 atoms/cm 2 with an uncertainty of 20%. 15 This value is close to the amount of trapped Cu. No silicide phase is observed in the cavities by XTEM in this study and atomic copper on the cavity walls cannot be directly measured by XTEM.…”
Section: Resultsmentioning
confidence: 55%
“…It is found that high dose He ϩ implantation can generate a wide microcavity band at the projected range without splitting the Si after annealing, while the H ϩ implantation dose range required to form microcavities without surface exfoliation is narrower. In our experiments, microcavities are not observed when the H dose is lower than 3 ϫ10 16 atoms/cm Ϫ2 , but on the other hand, the Si surface will be deformed during annealing if the H dose is higher than 4ϫ10 15 atoms/cm 2 . The XTEM observation demonstrate that the cracking of the H ϩ -implanted silicon is caused by the interaction of H with Si dangling bonds and breakage of the Si-Si bond forming ͑111͒ and ͑110͒ platelets.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The effectiveness of gettering depends on the establishment of gettering sites for absorbing impurities, the diffusion coefficients of the impurities in bulk Si, and the segregation coefficient of the impurities at the gettering sites [6]. An affordable technique for the creation of a defect free zone is the introduction of gettering sites from the wafer backside (ex: backgrinding [7], a layer of liquid aluminum [8], phosphorus diffusion at silicon oxide precipitates in the bulk [9], internal gettering at implantation-induced damage a few microns below the wafer surface [10], Fermi-level effect and heavily doped substrates of epitaxial wafers [11]. The removal of these metallic impurities from active device regions improves device yield, oxide integrity, and other device parameters.…”
Section: Introductionmentioning
confidence: 99%